APLIKASI PREDIKSI JUMLAH KONSUMSI BAHAN BAKAR MINYAK JENIS RON 88 PADA KENDARAAN RODA DUA DI KOTA PONTIANAK DENGAN MENGGUNAKAN RADIAL BASIS FUNCTION - , Syamsul Bahri, Annisa Alfajar , Fatma Agus Setyaningsih (Universitas Tanjungpura, 2017)
Fuel oil (BBM) is a very important needs to perform daily activities especially on motor vehicles. Fuel consumption , especially in Pontianak City have had a fall in change because the selling price of oil fuel which unstable. From these problems, this research will find which parameter that can produce the best training, and how to determine performance system best on a system prediction the number of fuel consumption premium by using the method Radial Basis Function. The purpose of this research is to search the parameters that produces best training and determine best performance of the system best system prediction on the number of premium fuel consumption using methods Radial Basis Function. The data used in this research was data number of motorcycles , large percent inflation kind of transport , the selling price of fuel oil and the number of fuel consumption in the Pontianak City. Based on the results of testing has been obtained the learning rate 0.01 capable of producing value mape of 6,2543 %. Â Kata kunciâ€” Fuel Oil, Radial Basis Function, MAPE.